Learning through movement and music exercise your smarts - Mitchell, Debby (Human Kinetics, 2012)
Kids love to move and it is proven that children learn academic concepts better when those concepts are combined with music and movement. So Debby Mitchell created a book and DVD package that includes video clips that combine learning with music and movement. The DVD also includes reproducible assessments, lyrics, and posters that can be used in the classroom to facilitate learning.